2018
DOI: 10.1097/pcc.0000000000001483
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Oxygen Metabolism Before and After RBC Transfusion in Infants Following Major Surgical Procedures

Abstract: Following RBC transfusion, cerebral oxygen saturation increases and cerebral fractional tissue oxygen extraction decreases. The data suggest that cerebral oxygenation in postoperative infants with cerebral fractional tissue oxygen extraction greater than or equal to 0.4 may be at risk in instable hemodynamic or respiratory situations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
3
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 33 publications
1
16
3
1
Order By: Relevance
“…In addition, Hb is an important factor in oxygen supply to the peripheral tissues and organs, including the brain; therefore, Hb level is expected to be associated with tissue rSO 2 . Thus far, in various clinical settings including hematology [44], surgery [45], pediatrics [4648], and HD therapy [49], cerebral rSO 2 has been shown to significantly increase in line with the increasing Hb levels following blood transfusion. On the other hand, it has been reported that there is no relationship between Hb concentration and cerebral rSO 2 values in HD patients with well-maintained Hb levels [15,17].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Hb is an important factor in oxygen supply to the peripheral tissues and organs, including the brain; therefore, Hb level is expected to be associated with tissue rSO 2 . Thus far, in various clinical settings including hematology [44], surgery [45], pediatrics [4648], and HD therapy [49], cerebral rSO 2 has been shown to significantly increase in line with the increasing Hb levels following blood transfusion. On the other hand, it has been reported that there is no relationship between Hb concentration and cerebral rSO 2 values in HD patients with well-maintained Hb levels [15,17].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study [46] on cerebral oxygen metabolism before and after major surgery including congenital cardiac repair in infants raised the question of the impact of transfusion threshold on cerebral fractional tissue oxygen extraction and hence, neurodevelopment outcome. According to the study, as no previous studies had investigated cerebral metabolism and neurodevelopment, the non-inferiority of restrictive transfusion strategy should be interpreted with caution.…”
Section: Discussionmentioning
confidence: 99%
“…Neunhoeffer et al [50] found a positive effect of red blood cell transfusion on FTOE and cerebral r-SO 2 in postsurgical infants, suggesting the feasibility of both parameters as transfusion triggers.…”
Section: Recent Developments In Near-infrared Spectroscopy Monitoringmentioning
confidence: 97%